Effect of number and different types of proton donors on excited-state intramolecular single and double proton transfer in bipyridine derivatives: Theoretical insights - Komsun Chaihan (2020)
© 2020 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique. Herein, the effects of the number (mono-PT and di-PT types) and different types of proton donors (hydroxyl (OH) and amino (NH2) groups) on the hydrogen bond strengths, electronic properties, and excited-state intramolecular single proton transfer (SPT) and double proton transfer (DPT) reactions in bipyridine derivatives were theoretically investigated using time-dependent density functional theory with both static calculations and dynamic simulations. The results of the static calculations show that the strength of the intramolecular hydrogen bond of all the studied molecules is stronger in the S1 state than that in the S0 state, which is supported by the red-shift in the corresponding vibrational mode and topology analysis. The effect of the number of proton donors causes the absorption peak of the mono-PT type to be blue-shifted, but its emission peak is red-shifted compared with that of the di-PT type. In contrast, the effect of different proton donors causes both the absorption and emission peaks in the molecules having OH groups to be blue-shifted compared with that with NH2 groups. The potential energy curves along the PT coordinates in the S1 state show that the mono-PT type has a lower PT barrier and are more exothermic than that of the di-PT type. The PT process in the molecules with an OH proton donor occurs easily than that in the molecules with an NH2 proton donor because of the lower PT barrier. Moreover, the 1st PT for SPT was found to be more favorable than the 2nd PT for DPT of the di-PT type due to its low PT barrier and exothermic reaction. Furthermore, the results of the dynamic simulations for the S1 state support that the occurrence of SPT and DPT is dependent on the PT barrier and reaction energy, in which the PT process is favorable with a low PT barrier and exothermic reaction but unfavorable with a high PT barrier and endothermic reaction. Therefore, the photophysical properties and PT processes of bipyridine derivatives can be tuned based on the number and type of proton donors.